2018
DOI: 10.1021/acs.jpclett.7b03316
|View full text |Cite
|
Sign up to set email alerts
|

How do London Dispersion Interactions Impact the Photochemical Processes of Molecular Switches?

Abstract: In the last two decades, linear-response time-dependent density functional theory (LR-TDDFT) has become one of the most widely used approaches for the computation of the excited-state properties of atoms and molecules. Despite its success in describing the photochemistry and the photophysics of a vast majority of molecular systems, its domain of applicability has been limited by several substantial drawbacks. Commonly identified problems of LR-TDDFT include the correct description of Rydberg states, charge-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…It proves that further research is required to draw more systematic observations on the nature and role of homopolar interactions in different types of systems. It shall be commented that conclusions drawn herein on the dispersion dominated stabilizing C–H⋯H–C interactions fit well to the most current findings,, , although such interactions, especially intramolecular ones, and their impact on the overall chemistry (structure and reactivity) are still poorly understood and more works are required to fully unveil their role and true nature in each case. For example, it has been recently reported that dihydrogen interactions can lead to the prolongation of phosphorescence lifetime in organic species .…”
Section: Resultssupporting
confidence: 83%
“…It proves that further research is required to draw more systematic observations on the nature and role of homopolar interactions in different types of systems. It shall be commented that conclusions drawn herein on the dispersion dominated stabilizing C–H⋯H–C interactions fit well to the most current findings,, , although such interactions, especially intramolecular ones, and their impact on the overall chemistry (structure and reactivity) are still poorly understood and more works are required to fully unveil their role and true nature in each case. For example, it has been recently reported that dihydrogen interactions can lead to the prolongation of phosphorescence lifetime in organic species .…”
Section: Resultssupporting
confidence: 83%
“…This seminal reformulation paves the way to first-principles modeling of molecules and materials and already captures, depending on the system, 99 per cent or more of the total electronic energy. † Unfortunately, the remaining fraction of the total electronic energy can be crucial for various observables and properties of interest, such as relative energies, [1][2][3][4] binding properties, [5][6][7][8][9] and structural features 3,4,10,11 as well as the mechanical, 12,13 thermodynamic, 4,14 kinetic, [15][16][17] and electronic 18,19 signatures of a given system. In the simple case of an Argon dimer for instance, KS-DFT calculation with the hybrid PBE0 functional captures about 99.95% of the total energy, but it gives no more than roughly 15% of the interaction energy.…”
Section: Troy Van Voorhismentioning
confidence: 99%
“…Within the framework of RPA, the ACFD formula (17) is typically not reformulated in terms of the non-local polarizability as done in Section 2.1, but stated in terms of the non-local density-density response, which according to eqn (19) is now fully defined by w l=0 . Solving eqn (19) and inserting the result into the ACFD formula (17) allows to analytically integrate over the coupling constant, l, and gives the expansion series for the full-range RPA correlation energy,…”
Section: Random-phase Approximation Of the Acfd Formulamentioning
confidence: 99%
“…While in the ground-state trans-stilbene derivatives the single bonds A and C are close to planarity, in the cis isomers planarity cannot be achieved because of the steric repulsion, which results in dihedral angles θ A/C between 140 and 155˚. It has recently been shown that for very bulky substituents like tert-butyl groups attached to the meta positions of the phenyl London dispersion interactions can play an important role while they are negligible in unsubstituted cis stilbene [ 63 ]. Populating the LUMO, thereby increasing the double bond character in bond A and C, leads to a significant increase in the dihedral angles θ A/C : 167.7˚ for θ C in 4c to 172.7˚ in 2c.…”
Section: Optimised Structures Charge Transfer Absorption and Fluorementioning
confidence: 99%